Author Correction: Microsatellite analysis for differentiating the origin of renal angiomyolipoma and involved regional lymph node. Issue 1 (December 2018) - Tan, Ping; Xu, Huan; Jiang, Yong; Yang, Lu; Zou, Yan; Liu, Liangren; Liu, Nian; Cao, Dehong; Fan, Yu; Li, Qiyuan; Wei, Qiang
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.